A dual-band high gain complementary split- ring resonator (CSRR) loaded hexagonal bowtie antenna with enhanced bandwidth for Vehicle- to-Vehicle (V2V) communication applications - Alsisi, Rayan Hamza; Vallappil, Arshad Karimbu; Wajid, Hafiz Abdul (International Journal of Electrical and Computer Engineering Systems, 2022)
A highly reliable and efficient communication system is needed for a vehicle to navigate and drive to the destination without human control (known as an autonomous or self-driving vehicle). In this work, we consider various parameters for the antenna design, ensuring reliable communication amongst vehicles and infrastructure. Specifically, we consider the type of antenna, the method used, operating frequency, substrate type (with thickness and permittivity), size and shape, gain, and bandwidth. An optimal threshold value or range of these parameters is identified. Moreover, a complementary split-ring resonator (CSRR) metamaterial (MTM) based hexagonal bowtie antenna for a high gain V2V communication environment is presented. This antenna covers sub- 6 GHz fifth generation (5G) bands (3.15-3.95 GHz) and Wi-Fi band 2.4GHz. Printing was done on a low-cost FR4 substrate for the radiating patch. Antenna Bandwidth is enhanced using a partial ground plane. The radiating layer is based on hexagonal patches printed on the double side of the substrate, and the CSSR structure is etched from patches to enrich antenna gain and bandwidth. More importantly, the proposed CSRR employed antenna provides gain and bandwidth of 1.6dBi / 6 dBi and 100MHz/ 8000MHz at 2.4GHz /3.5GHz, respectively. A highly known software, CST microwave studio, simulates the proposed antenna. Simulated and measured results make this arrangement a potential candidate for 5G high gain V2V communication.